Identification of Specific Hemopexin-like Domain Residues That Facilitate Matrix Metalloproteinase Collagenolytic Activity - Lauer-Fields, Janelle L. (American Society for Biochemistry and Molecular Biology, 2009)
Collagen serves as a structural scaffold and a barrier between tissues, and thus collagen catabolism (collagenolysis) is required to be a tightly regulated process in normal physiology. In turn, the destruction or damage of collagen during pathological states plays a role in tumor growth and invasion, cartilage degradation, or atherosclerotic plaque formation and rupture. Several members of the matrix metalloproteinase (MMP) family catalyze the hydrolysis of collagen triple helical structure. This study has utilized triple helical peptide (THP) substrates and inhibitors to dissect MMP-1 collagenolytic behavior. Analysis of MMP-1/THP interactions by hydrogen/deuterium exchange mass spectrometry followed by evaluation of wild type and mutant MMP-1 kinetics led to the identification of three noncatalytic regions in MMP-1 (residues 285–295, 302–316, and 437–457) and two specific residues (Ile-290 and Arg-291) that participate in collagenolysis. Ile-290 and Arg-291 contribute to recognition of triple helical structure and facilitate both the binding and catalysis of the triple helix. Evidence from this study and prior studies indicates that the MMP-1 catalytic and hemopexin-like domains collaborate in collagen catabolism by properly aligning the triple helix and coupling conformational states to facilitate hydrolysis. This study is the first to document the roles of specific residues within the MMP-1 hemopexin-like domain in substrate binding and turnover. Noncatalytic sites, such as those identified here, can ultimately be utilized to create THP inhibitors that target MMPs implicated in disease progression while sparing proteases with host-beneficial functions.